Helicobacter pylori Infection and Anemia in Taiwanese Adults - Hsiang-Yao Shih; Fu-Chen Kuo; Sophie S. W. Wang; Yi-Chang Liu; Meng-Chieh Wu; Yang-Pei Chang; Guei-Fen Chiu; Pi-Yu Chang; Deng-Chyang Wu; Ming-Chia Hsieh; Yao-Li Chen (Gastroenterology Research and Practice)
Background. Chronic Helicobacter pylori infection and iron-deficiency anemia (IDA) are common in adults. Although the most common causes of IDA usually arise from the gastrointestinal tract, the association between chronic Helicobacter pylori infection and anemia remains unclear. Aim. To evaluate the association of chronic Helicobacter pylori infection and IDA. Materials and Methods. We enrolled 882 patients from January 2010 to April 2013. The status of Helicobacter pylori (H.p) infection was confirmed and blood samples from the same participants were taken on the same day to check the level of hemoglobin, serum iron, ferritin, and total iron-binding capacity (TIBC). Results. No significant difference was noted from the demographic data. The average level of hemoglobin (Hb) was not different between negative and positive groups, pos 13.57 g/dL versus neg 13.65 g/dL (P=0.699). Although the levels of serum IDA related parameters were expected in positive group (lower serum iron and ferritin and higher TIBC) these differences did not reach statistical significance (P=0.824 for iron, P=0.360 for ferritin, and P=0.252 for TIBC). Conclusion. Chronic Helicobacter pylori infection is not attributed to IDA. The levels of hemoglobin, serum iron and ferritin, and TIBC remain unaffected after chronic H.p infection. Large-scale clinical studies are needed to prove the association.